JANE AUSTEN IS SHINING EXAMPLE OF ENGLISH LITERATURE - Dinara Umurzakova; S.S. Nishonova (TADQIQOTLAR.UZ, 2024)
Annotation: Jane Austen, born in 1775, remains a revered figure in literature for her enduring novels like "Pride and Prejudice" and "Sense and Sensibility." Known for her sharp wit and insightful portrayal of societal intricacies, Austen's works feature strong female characters who defy conventional norms, making her narratives both engaging and thought-provoking. Through her elegant prose and astute social critique, Austen's writings transcend their historical settings, offering timeless reflections on the complexities of the human experience, captivating readers across generations and cultures.